Uncommon Horse Sense: Review of Erin McKenna, Pets, People, and Pragmatism - Kelleher, Hillary (Humanimalia, 2014)
Erin McKenna. Pets, People, and Pragmatism. New York: Fordham UP, 2013. ix + 247 pp. 85 hc, 26 pb.